A influência do lugar na obra de Álvaro Siza - Conto, Vanessa de (2023)
The dissertation presents a critical and investigative approach to the relationship between architecture and place established by Álvaro Siza (1933-) in two museums built in the 21st century. Thus, the general objective is to understand how the place influenced the definition of the architectural approach in the projects of the Fundação Iberê Camargo (1998-2008), Porto Alegre, Brazil, and the Museu de Arte Contemporânea Nadir Afonso (2006-16), Chaves, Portugal. The place is considered a fundamental issue for the definition, characterization and essence of the aforementioned projects. In addition, the motivation for choosing the buildings stems from their exceptionality, architectural pedagogical content and relevance in the museological panorama. After the theoretical-critical contribution, the Contemporary Quaternary was used as a methodology for the analysis of the characteristics of the place, the architectural approach and the tectonics. In the end, the research enabled the identification of recurrent morphological and compositional decisions, as well as the understanding of Álvaro Siza's ability to reinterpret references, derived from his works, Modern Architecture and the place, reflected in different ways, such as in the implantation, in the paths, in the materiality or in the volumetric aspects. The result is buildings that maintain a critical relationship with the surroundings and with their own geometry, evidencing their commitment to the preservation of the place and the transformations imposed by architecture. In both projects, the potential of the contemporary museum to overcome the function of a mere art container is evident, integrating them into cities as centers of culture and leisure.